#### Answer

$176$

#### Work Step by Step

$\sum_{i=3}^6 (2i^2+1)$
$=(2*3^2+1)+(2*4^2+1)+(2*5^2+1)+(2*6^2+1)$
$=19+33+51+73$
$=176$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$176$

$\sum_{i=3}^6 (2i^2+1)$
$=(2*3^2+1)+(2*4^2+1)+(2*5^2+1)+(2*6^2+1)$
$=19+33+51+73$
$=176$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.